Tradução, adaptação e validação da Mishel Uncertainty in Illness Scale for Family Members: aplicação em familiares de pessoas com paraplegia - Barbosa, Islene Victor (2012)
Uncertainty is the inability of the person to deter mine the meaning of the disease-related events. This is a methodological study that aimed t o translate, culturally adapt to Portuguese and validate the Mishel Uncertainty in I llness Scale for Family Members of people with spinal cord injury and motor deficit li ke paraplegia, and also verify the reliability and validity of the Mishel Uncertainty in Illness Scale for Family Members (PPUS-MF). The sample consisted of 152 relatives of inpatients with spinal cord injury. Data collection happened in a public hospital refer ence for trauma in Fortaleza-CE, Brazil, from January to July 2012, through interviews using a questionnaire to collect socio- demographic data and then apply the final version i n Portuguese of the PPUS-MF scale. The scale questionnaire is presented according to L ikert scale: strongly disagree (1), disagree (2), undecided (3), agree (4) and strongly agree (5). The adaptation process followed the steps recommended in the literature. T he PPUS-FM allows measuring the uncertainty level of family members of a sick perso n. The scale is self-administered, it has 31 items and the score is calculated by adding up t he answers with higher scores indicating higher levels of uncertainty and the score ranges f rom 31-155. The higher the score, the greater the uncertainty of family members regarding the disease. The 31 items are divided into four domains: Ambiguity, Lack of Clarity, Lack of Information and Unpredictability. The psychometric properties analyzed were: content validity (committee of experts); construct validity (confirmatory factor analysis an d comparison of the factors average and total scores according to socio-demographic variabl es of the family members in the study); reliability (test-retest and Cronbach's alpha). The ethical and legal aspects were considered. The results revealed that most participants were fe male, 85 (55.9%), with average age of 42.8 years, regarding the relationship 45 (29.8%) w ere siblings, followed by mother 27 (17.9%) and wife 26 (17.2%). Of these 84 (55.3%) co me from the interior of the State, 116 (76.3%) have a partner and 68 (44.7%) had 4-8 years of study with an average of 8.78 years and 104 (68.4%) perform work activities. In t he assessment of psychometric properties, we emphasize that in the confirmatory f actor analysis, adjustments were made excluding the items 4, 9, 14, 24, 25 and 27. Of the se, the items 4, 24 and 25 belong to the Ambiguity domain, items 9 and 14 to the Lack of Cla rity and item 27 to the Unpredictability. Even with the items exclusion the re was a super adjustment in data to obtain convergence. The translated version of PPUS- MF presented very low scores of Cronbach's alpha in its domains: Ambiguity (0.54), Lack of Clarity (0.41), Lack of Information (0.40) and Unpredictability (0.29). We adjusted the data in the confirmatory factor analysis to obtain the convergence, revealin g that the MUIS-FM is acceptable and parsimonious set to the original model. The coeffic ients for the domains were low; such results enabled us to assume that the items seem to represent phenomena that cannot be reduced to more synthetic measurements, especially when measuring a psychological construct. Therefore, we concluded that we obtained a valid and reliable instrument capable of being applied to family members of patie nts admitted with spinal cord injury, pointing the aspects and domains of their uncertain ties